2013
DOI: 10.1111/jocn.12359
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Morse Fall Scale implemented in an electronic medical record system

Abstract: The study results recommend practice change in fall prevention. As the validity was highest when the patient was first classified into the high-risk group based on the Morse Fall Scale cut-off score 51, patients classified as high risk should be placed under special nursing interventions until the day of their discharge, regardless of change in the patient state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 16 publications
1
52
0
6
Order By: Relevance
“…The validity of the IFRST was assessed according to sensitivity, specificity, positive and negative predictive values and the area under the ROC curve (AUC; Zweig & Campbell 1993). Because the Youden index is an analytic method commonly used for most diagnostic tests, especially for fall assessment tools (Wong Shee et al 2012, Baek et al 2014, Lee et al 2016, it was used for indicating the most appropriate cut-off points for the IFRST (Youden 1950). The Youden index is calculated by subtracting 1 from the sum of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The validity of the IFRST was assessed according to sensitivity, specificity, positive and negative predictive values and the area under the ROC curve (AUC; Zweig & Campbell 1993). Because the Youden index is an analytic method commonly used for most diagnostic tests, especially for fall assessment tools (Wong Shee et al 2012, Baek et al 2014, Lee et al 2016, it was used for indicating the most appropriate cut-off points for the IFRST (Youden 1950). The Youden index is calculated by subtracting 1 from the sum of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The Youden index is calculated by subtracting 1 from the sum of sensitivity and specificity. Possible values range from À1 to 1, where a higher value indicates greater effectiveness in predicting an actual fall/ nonfall (Baek et al 2014). The combination of the ROC curve and Youden index could provide an appropriate cutoff point balancing sensitivity and specificity to distinguish patients diagnosed as fallers and nonfallers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal cut-off value ranges between of 25 -55, with the standard cut-off value of 45 suggested by the creators of the tool [8]. Studies have found different cut-off values to be optimal in different organizations [9] [10]. The organization in which this analysis was conducted found the cut-off value of 45 to be optimal based on a statistical analysis of the specificity and sensitivity of each potential cut off value.…”
Section: Fall Risk Assessmentmentioning
confidence: 99%